Association of hormone receptor status with grading, age of onset, and tumor size in BRCA1-associated breast cancer - Graeser, M.; Bosse, K.; Brosig, M.; Engel, Christoph; Schmutzler, R. K. (Virchows Archiv : an international journal of pathology, 2009)
BRCA1-associated breast cancer frequently presents with estrogen-receptor (ERalpha) and progesterone-receptor (PR) negativity, grade 3, and early onset. In contrast, in BRCA1-deficient mice, ERalpha is highly expressed in early tumorigenesis. In a retrospective cohort study on 587 breast cancer patients with deleterious BRCA1 mutations, the correlation of ER, PR status, grading, age of onset, and tumor size was investigated. ERalpha and PR expression decreased from 62% in ductal carcinoma in situ (DCIS) to 20% and 16% in pT3, respectively (p value for ER 0.025 and PR 0.035, Fisher’s exact test). The percentage of grade 1/2 tumors decreased from 44% in DCIS to 17% in pT3 (p value 0.074). Moreover, ER/PR positivity increased with increasing age. Our data suggest that early stage BRCA1-associated breast cancers are more frequently ERalpha and PR positive and low grade than advanced stages.